Walking the good road of life: a longitudinal evaluation of American Indian youth suicide prevention training - Small, Clayton; Horn, Ernie Big; Small, Geri; Webb, Kellie; Bull, Edwina Brown; Small, Maha Charani; Face, Ruthie Cedar; Pourier, Warren; Montileaux, Hawkeye; Christiansen, Lance; Bradley, Brian; Trottier, Wayne; et al. (Frontiers in Public Health, 2025)
BackgroundAmerican Indian/Alaska Native (AI/AN) populations have the highest suicide rate in the United States. Research on effective, culturally-centered, multi-level approaches to prevent suicide in AI/AN populations are limited.MethodsThis multi-site longitudinal evaluation employed a retrospective pre-posttest design, utilizing a self-report survey administered daily following the training. Daily surveys included four areas related to suicide prevention, holistic wellness, generational knowledge, behavior change, and legacy impacts. The first objective of this study was to explore how the Good Road of Life training impacted participant knowledge regarding suicide and related risk factors while also exploring protective behaviors and impacts from a culturally-centered, strengths-based lens. A second objective was to present a conceptual model grounded in socioecological and trans-ecological theories of GRL for collective healing targeting the individual, family, community, Tribe, and nation to prevent suicide.ResultsBetween 2019 and 2024, 27 GRL trainings were conducted at 8 Tribal sites in Montana, South Dakota, North Dakota, and Wyoming. Data accumulated across these 27 trainings and 1,810 students represented diverse tribes, locations, and ages. Students were asked to rate different domains of Holistic Wellness: mental (M = 3.25, SD = 1.03), physical (M = 3.33, SD = 1.03), spiritual (M = 3.35, SD = 1.05), and emotional (M = 3.17, SD = 1.12). Students rated 17 generational knowledge domains before and after GRL training; all comparisons were significant at p < 0.001; all differences had moderate or large effect sizes. Middle school students reported larger increases in knowledge from pre to post than high school students.DiscussionFindings from this evaluation underscore the importance of early intervention, culturally-centered approaches, and community-led suicide prevention in AI/AN populations.